Frequency of primiparous mother initiated breastfeeding earlier after birth and factors associated with it in Sindh, Pakistan: a secondary analysis - Bham, Asma A.; Sharma, Sucheta; Sardool, Akash; Mujahid, Umer F.; Ayaz, Amrat; Valliani, Komal; Maredia, Nawaal (International Journal Of Community Medicine And Public Health, 2021)
Background: Initiation of breastfeeding within one hour after delivery plays a vital role in a newborns life by not only increasing their survival rate but also reducing many life-threatening diseases in the newborn. The aim of the study was to determine frequency of early initiation of breastfeeding among primiparous mothers in a rural district of Thatta, Pakistan. Methods: This study was conducted using survey data extracted from a cross-sectional study conducted in 2019 on prevalence of exclusive breastfeeding and factors associated with it among women in Thatta. The outcome was early initiation of breastfeeding. To determine factors associated with it, multi variable logistic regression was carried out. Results: The study showed that 30.3% of primiparous mothers in Thatta initiated breastfeeding within one hour of birth and knowledge of mothers (OR=9.76, 95% CI: 1.99-17.59), place of birth (OR=3.51, 95% CI: 1.32-9.31) and support of health care professional at health facility (OR=2.93, 95% CI: 1.09-7.86) are the factors significantly associated with early initiation of breastfeeding among primiparous mothers. Conclusions: In order to enhance the early initiation of breastfeeding, it is important for health care professionals to emphasize on the effect of pre-lacteal feeding during and support breastfeeding immediately after delivery, especially among women who had given birth for the first time.